Um outro junho : o movimento #NãoVaiTerCopa, o diálogo no Twitter e as controvérsias sobre a Copa do Mundo de 2014 - Medeiros, Jean Maicon Rickes (2016)
This dissertation has the intention to do an analysis of the posts, tweets, made by users of the social network, Twitter, on the World Cup FIFA TM 2014 and the controversies formed for the preparation, organization and hosting of the event in Brazil. Thus, the research consists to address a theoretical framework involving the concepts needed to support the processes used for the completion of this work’s objectives. The central axis in this dissertation is developed by the sociologist Bruno Latour and it’s called Actor-Network Theory, which brings with it an idea that is opposed to the “sociology of the social”, and so involving and considering an analysis of the social with hierarchically equivalent actions between human actors and not human in their associations. This diversity in associations reveals the networks formed between these actors. Such networks can be mapped through the empirical technique of this theory, called Cartography of controversies. This technique is part of the methodology used in this study formalizing the analytical processes of the networks formed by the profiles and their interactions. The discussion takes place around the hashtag #NaoVaiTerCopa and its terms spread widely in the controversies around the World Cup, the analysis of the actors that it involves and the perspectives exposed in the networks formed by them.